The Functions of the Artistic Detail in I. Bunin’s «Dark Avenues» Series - SARGSYAN, RUZANNA (Bulletin of Yerevan University H: Russian Philology, 2021)
It is shown in the paper that external details perform an artistic function and take their part in the creation of landscapes and portraits and can form the implication of the character. They also carry out a characteristic function which expresses feelings and emotions of heroes. The detail in Bunin’s series has an implicit function as well, which reveals the meaning of the character and the underlying theme. One and the same detail can often be seen in different short stories, thus acquiring the status of a symbol.